If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 12) = 8x + 6 Reorder the terms: 3(12 + x) = 8x + 6 (12 * 3 + x * 3) = 8x + 6 (36 + 3x) = 8x + 6 Reorder the terms: 36 + 3x = 6 + 8x Solving 36 + 3x = 6 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 36 + 3x + -8x = 6 + 8x + -8x Combine like terms: 3x + -8x = -5x 36 + -5x = 6 + 8x + -8x Combine like terms: 8x + -8x = 0 36 + -5x = 6 + 0 36 + -5x = 6 Add '-36' to each side of the equation. 36 + -36 + -5x = 6 + -36 Combine like terms: 36 + -36 = 0 0 + -5x = 6 + -36 -5x = 6 + -36 Combine like terms: 6 + -36 = -30 -5x = -30 Divide each side by '-5'. x = 6 Simplifying x = 6
| 5x-8+3x+3x+5x-8=-4 | | 10x+1(100)=8x+800 | | 4x+6(-x+8)=60 | | -3x+8=9x-3 | | 4(1-4p)+1=-91 | | -12=8y+4 | | 3(2x+1)+4(3x+1)=17 | | 3d+7=2d-7 | | 3x+700=x+1000 | | -5+2x=-25 | | 4(d+2)+-2d=3(2+d) | | 5g+19=8+5g | | (x^3-4x^2+3x-2)=0 | | lim(x^3-4x^2+3x-2)=0 | | -5x-6x=22x | | 20x+5=160+5 | | 3x+4=5x-10+-4 | | 5(3+2)=4(x-2) | | 20x+20x=20(7) | | -6(5+4n)=66 | | 8(y+7)=7y-2 | | 597-597= | | S=7r+2 | | 8(r-3)-7(r-1)=2(r+6) | | yw+yq=x | | 8x-y+2y= | | 4.8x-3.7y=1.7 | | 252=12(3x+1) | | 1/3(n+2)=9 | | t^2+5.5t-20=0 | | -5(2+3m)=-100 | | 100w=-300 |